Sensitivity of the berg balance scale in patients with osteoarthritis Sensibilidade da Escala de Equilíbrio de Berg em indivíduos com osteoartrite - Da Silva Souza A.C.* (2012)
The study has aim of analyze the sensitivity of the (BBS) to detect the risk of falling in individuals with knee osteoarthritis (KOA), and to investigate an association between functional capacity, KOA degree, pain, index of fear of falling, and history of falls with the BBS score. Method: Participants were 69 individuals with KOA. The BBS 45, 47, 49, 51 and 53 cut-off points were used to analyze sensitivity and specificity of the test. The WOMAC questionnaire, Falls Efficacy Scale International (FES-I) and visual analog scale were herein used. The results showed significant differences between the KOA groups with and without history of falls. The BBS showed a strong correlation between the Womac and the FES-I, and moderate correlation between history of falls and KOA degree. The BBS did not show an ideal cut-off point for individuals with KOA. However, the scale is sensitive to individual differences in this population.